Hepatoprotective effects of Gentianella turkestanerum extracts on acute liver injury induced by carbon tetrachloride in mice - Yang, Jianghua (Am J Transl Res, 2017)
Objective: To investigate the contents of secoiridoid compounds (i.e. sweroside, swertiamarin and gentiopicrin) from Gentianella turkestanerum extracts, and the potential effects of G. turkestanerum extracts against carbon tetrachloride (CCl(4)) induced liver injury in mice. Methods: The contents of swertiamarin, gentiopicroside and sweroside from different G. turkestanerum extracts were determined with high performance liquid chromatography (HPLC). CCl(4) was used to induce acute liver injury in mice. The serum aspartate amino transferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), total protein (TP), total bilirubin (TB), superoxide dismutase (SOD), malondialdehyde (MDA), glutathione transferase (GSH) and catalase (CAT) were measured. HE staining was performed to investigate the pathological changes of liver. Results: Iridoid glycoside showed the highest content in the product extracted by butanol (designated as GBA), but lower in the products extracted by ethyl acetate and water designated as GEA and GW, respectively. All G. turkestanerum extracts showed protective effects against CCl(4) induced acute liver injury in mice, among which GBA showed the maximal protective effects. G. turkestanerum extracts induced significant decrease in the serum ALT, AST, ALP and TB compared with those in the mice with acute lung injury (P < 0.01). Obvious increase was noticed in serum TP (P < 0.01). Moreover, such effects presented in a dose-dependent manner. Compared with the control group, the MDA was significantly elevated in the model group (P < 0.01), while significant decrease was observed in the levels of SOD, GSH and CAT in model group compared with the control group (P < 0.01). Whereas, such phenomenon was completely reversed by G. turkestanerum extracts in a dose-dependent manner. Conclusion: G. turkestanerum showed protective effects against CCl(4) induced acute liver injury in mice.